Wood identification and acoustic analysis of three original Aztec teponaztli musical instruments - Herrera-Castro, Mariano; Quintanar-Isaías, Alejandra; Orduña-Bustamante, Felipe; Olmedo-Vera, Bertina; Jaramillo-Pérez, Ana Teresa (Instituto de Ecología, A.C., 2019)
Teponaztlis exhibited in Mexico’s Anthropology Museum are the most emblematic items among Aztec musical instruments. The purpose of this research was twofold: to correctly identify the wood used to manufacture three of the most important instruments of their kind and to perform an acoustic analysis to determine relevant acoustic and musical parameters of these instruments. Wood identification consisted in comparing some anatomical features of teponaztlis to those of known species from a wood collection and other sources. Multivariate analysis shows that species are separated by the percentage of uniseriate and partially biseriate rays at one hand and by fibre wall thickness at the other hand. The results show that the genus Dalbergia was used for these instruments, and the analysis suggests proximity of teponaztlis to Dalbergia palo-escrito, and to D. granadillo. The acoustic analysis was based on digital sound recordings of the instruments played with the under-side cavity closed or open. Results show that musical intervals between the two low and high pitch tones of the instruments are from slightly below a major third, to slightly above a fifth. Tones produced with the under-side cavity closed are slightly shorter in duration, and stronger, in comparison when it is open. Playing one of the two tones faintly produces sound from the other, and also from the sides of the instrument, especially with the under-side cavity open. The musical intervals that are observed in these instruments do not correspond exactly to conventional Western tunings.